2022
DOI: 10.1149/10701.11643ecst
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Diffusivity Measurement of MoS2 & MoS2-GO Nano-Composite By Photoacoustic Spectroscopy

Abstract: Photoacoustic spectrometer (PAS) is a significant technique to measure the thermal diffusivity of any material. When modulated light interact with solid sample which is covered by aluminium or other metal plate, first the light is absorbed by the sample and then thermal energy emitted due to non-radiative decay. Thereafter, acoustic wave produced due to different temperature which maintain by an optical chopper. The medium inside the cavity expands or retract according to the chopper frequency. So, the generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…12 Through PAS the thermal diffusivity could efficiently be measured and it is also used as multi-purpose spectroscopic technique in variety of scientific fields. [13][14][15][16][17] With the advent of lasers and sensitive acoustic sensors the sensitivity of PAS has now improved too much.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Through PAS the thermal diffusivity could efficiently be measured and it is also used as multi-purpose spectroscopic technique in variety of scientific fields. [13][14][15][16][17] With the advent of lasers and sensitive acoustic sensors the sensitivity of PAS has now improved too much.…”
Section: Introductionmentioning
confidence: 99%
“…Schmitt et al 14 have measured the thermal diffusivity of caprocks and Jeyadheepan et al 15 have measured the thermal diffusivity of Cd 2 SnO 4 thin films using this technique. Sarkar and Kumar 16,17 have measured the thermal diffusivity of MoS 2 , MoS 2 -GO nano-composites, and carbon black samples. Authors have found that the addition of GO in MoS 2 increases the thermal diffusivity and this result has inspired authors to measure thermal diffusivity of graphene oxide (GO).…”
Section: Introductionmentioning
confidence: 99%